Training manual on approach to unwell children under 5 years - Hii, King Chin; Abdul Manaf, Aina Mariana; George, George Mathew; Omar, Juslina; Thiagarajan, Anuradha; Yusof, Yusnita; Lim, Jean-Li; Kamaruzaman, Nor Azam; Abd. Kadir, Rohaiza; Supian, Ziti Akhtar; Zakaria, Nik Suhaila; Suzila, Azainor; et al. (Ministry of Health, 2020)
In line with the SDG, Ministry of Health Malaysia aims to end all preventable deaths among newborn and children under 5 years and developed the ‘Training Manual on Approach to Unwell Children under 5 years’ (ATUCU5) based on the WHO IMCI strategy. ATUCU5 is meant for training of our health care providers on three main components, which includes early detection of danger signs, improvements in the case management skills and proper immediate treatment.